The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s12262-013-1031-0
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Primary Malignancies in Breast and Kidney: A Rare Case Report

Abstract: Multiple synchronous malignancies are rarer than metachronous ones. Primary synchronous breast and renal cancer is even rare. Such a case requires strict exclusion of possible metastasis to either site and to confirm the primary nature of each malignancy for better outcome of management and survival benefit. Multiple primary synchronous malignancies may be due to shared genetic mutations if any common carcinogenic factor cannot be found. The role of estrogens in cases in which human renal carcinoma is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…6 The incidence of dual primary malignancy (any origin) is roughly 4-11%. 7,9 According to Jiao et al there have been 8 reported cases of synchronous breast primary malignancy coexisting with RCC. 10,18 Most of the multiple malignancies reported in literature are metastatic tumours or metachronous breast malignancy with RCC.…”
Section: Discussionmentioning
confidence: 99%
“…6 The incidence of dual primary malignancy (any origin) is roughly 4-11%. 7,9 According to Jiao et al there have been 8 reported cases of synchronous breast primary malignancy coexisting with RCC. 10,18 Most of the multiple malignancies reported in literature are metastatic tumours or metachronous breast malignancy with RCC.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant presence of breast cancer with one or more other type of cancers such as the colon, vulva, lung, larynx, liver, uterus and kidneys has been presented in the literature (4). The association of kidney cancer with synchronous and metachronous cancer in similar organs has been reported in the literature (1,5). However, reports on synchronous breast and renal cancer are very uncommon (1,4).…”
Section: Introductionmentioning
confidence: 95%
“…The association of kidney cancer with synchronous and metachronous cancer in similar organs has been reported in the literature (1,5). However, reports on synchronous breast and renal cancer are very uncommon (1,4).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Synchronous tumors are defined as two tumors arising concurrently or within six months of diagnosis [1]. Reports of synchronous RCC and breast cancer are limited to nonmetastatic RCC and hormone receptor-positive infiltrative ductal carcinoma (IDC) treated with complete resection of each primary tumor followed by chemoradiation and hormone therapy [2, 3]. We present a case of tailored immunotherapy for a patient with concurrent metastatic RCC (mRCC) and triple-negative breast cancer (TNBC).…”
Section: Introductionmentioning
confidence: 99%